Aprendizagem da docência: um estudo a partir do atendimento escolar hospitalar - Covic, Amália Neide (2008)
This study contributes with the knowledge construction related to the learning to teach in an hospital context that have differences from the traditional classroom. These assumptions need to be made: (i) When scholar quotidian actions are enunciated there exists docent learning; (ii)The enunciations of the scholar quotidian actions, when seem as cultural artifacts, can be investigated; and (iii) the docent space of practices is considered a strategy of learning. This research focus in this question: What are the possibilities that the practical enunciations made by intern teachers in an hospital environment promote the docent learning? The search to answer this question is sustained by studies with strong qualitative methodology, oriented in the investigation of the meanings construction in a space which the communicative action takes the place of the experiment. The data for this study comes from the modular discursive analysis and from the study of the Habermas Theory of Communicative Action. The enunciations used in this research comes from a group of eight teachers and eight intern teachers of the IOP-GRAACC-UNIFESP from june 2005 to july 2006. It´s possible to observe that, in the enunciations of the actions used in this study, the group: creates new meanings to the implicit docent knowledge related to the institutional space of Health and Education; there are tendencies of traditional curriculum adaption to the hospital reality; investigation spaces are created in the process; there are arguments for consensus when spaces are open for differences and mobilization of the action; the properties appears as the environment adaptabilities are created; specific curriculum are constructed for the patient-students in oncology treatment; signifies the position of the Hospital School sphere of actions; create a relation of inclusion in the hospital space; investigates the practice with autonomy construction of the docent; space construction for docents; and mobilize knowledges linked to solidarity